Genomic landscape and evolutionary trajectories of ovarian cancer precursor lesions. Issue 1 (15th February 2019) - Wu, Ren‐Chin; Wang, Pei; Lin, Shiou‐Fu; Zhang, Ming; Song, Qianqian; Chu, Tiffany; Wang, Brant G; Kurman, Robert J; Vang, Russell; Kinzler, Kenneth; Tomasetti, Cristian; Jiao, Yuchen; et al.
Abstract: The clonal relationship between ovarian high‐grade serous carcinoma (HGSC) and its presumed precursor lesion, serous tubal intraepithelial carcinoma (STIC), has been reported. However, when analyzing patients with concurrent ovarian carcinoma and tubal lesion, the extensive carcinoma tissues present at diagnosis may have effaced the natural habitat of precursor clone(s), obscuring tumor clonal evolutionary history, or may have disseminated to anatomically adjacent fimbriae ends, masquerading as precursor lesions. To circumvent these limitations, we analyzed the genomic landscape of incidental tubal precursor lesions including p53 signature, dormant STIC or serous tubal intraepithelial lesion (STIL) and proliferative STIC in women without ovarian carcinoma or any cancer diagnosis using whole‐exome sequencing and amplicon sequencing. In three of the four cancer‐free women with multiple discrete tubal lesions we observed non‐identical TP53 mutations between precursor lesions from the same individual. In one of the four women with co‐existing ovarian HGSC and tubal precursor lesion we found non‐identical TP53 mutations and a lack of common mutations shared between her precursor lesion and carcinoma. Analyzing the evolutionary history of multiple tubal lesions in the same four patients with concurrent ovarian carcinoma indicated distinct evolution trajectories. Collectively, the results support diverse clonal origins of tubal precursor lesions at the very early stages of tumorigenesis. Mathematical modeling based on lesion‐specific proliferation rates indicated that p53 signature and dormant STIC may take a prolonged time (two decades or more) to develop into STIC, whereas STIC may progress to carcinoma in a much shorter time (6 years). The above findings may have implications for future research aimed at prevention and early detection of ovarian cancer. Copyright © 2019 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.